Permian brachiopods from South Primorye, Far East Russia: systematics, palaeobiogeographical and palaeoceanographical implications. Issue 1 (2nd January 2022) - Shi, G.R.; Lee, Sangmin; Kotlyar, Galina V.; Zakharov, Yuri D.
Abstract: The South Primorye area of Far East Russia has long been recognized for its highly diverse mid-Permian brachiopod fauna; however, a taxonomic and palaeobiogeographical reassessment is overdue. This paper describes two brachiopod assemblages from the Barabash and Pilnikov section localities in South Primorye. The Barabash section assemblage was collected from the lower part of the Barabashevka Formation and includes 18 brachiopod species associated with other marine faunas indicative of the late Wordian. Alternatively, the Pilnikov section assemblage derives from the Pilnikov Formation and yields four brachiopod species consistent with the mid-Kungurian (Irenian). The palaeobiogeographical composition of the Barabash assemblage is distinguished by a conspicuous admixture of cool-water Boreal Realm elements and palaeoequatorial warm-water Cathaysian Province elements, together with genera that have antitropical distributions. Comparisons with analogous Neogene faunas from the Sea of Japan/East Sea suggest that the Barabash section might have been situated in the eastern part of the Sino-Mongolian seaway, which was located in an equivalent mid-latitude northern temperate confluence of warm- and cold-water ocean currents. G. R. Shi * [guang@uow.edu.au ] and Sangmin Lee [sangminlee76@gmail.com ], School of Earth, Atmospheric and Life Sciences, University of Wollongong, Northfields Ave, Wollongong, NSW 2522, Australia; Galina V. Kotlyar [galina_kotlyar@vsegei.ru ], Karpinsky All Russian Research Geological Institute (VSEGEI), Srednii pr. 74, St. Petersburg, 199106 Russia; Yuri D. Zakharov [ yurizakh@mail.ru ], Far East Geological Institute, Far East Branch, Russian Academy of Sciences, Vladivostok, 690022 Russia.